Effectiveness of protected areas in the conservation of mammal species in the Pantanal biome - Sonoda, Fátima Aparecida; Silva, Priscilla Barbosa Alcantara da; Ribeiro, Laura Rodrigues; Tocantins, Nely; Torrecilha, Sylvia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Protected areas (PA) are recognized as the main strategy of biodiversity in situ conservation and used as a valid and measurable indicator of progress in remaining worldwide biodiversity conservation. Thus, the objective of this article was to conduct a detailed literature review to accumulate records of mammal occurrence across Pantanal Conservation Units and to evaluate their effectiveness in protecting the species present in the biome. We recorded 112 species in the biome’s Integral Protection Conservation Units. A total of 125 species was obtained by adding up the records of the biome’s Sustainable Use Conservation Units. The biome’s Integral Protection Conservation Units presents records of approximately 68% of the species listed for the Pantanal biome. Added to the biome’s Sustainable Use Conservation Units’ records, approximately 76% of the species were recorded. Of 22 threatened species analyzed, there was at least one record in the biome’s Integral Protection Conservation Units network. Our results reinforce the importance of a PAs network approach based on broad management and conservation objectives as the main strategy to ensure the sustainability of the biome, which is still poorly represented in the National System of Conservation Units (4.65% of its territory protected).